2008
DOI: 10.1007/s00134-008-1288-0
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus is an independent risk factor for ICU-acquired bloodstream infections

Abstract: Despite strict glycemic control, diabetic patients have a 1.7-fold probability of developing an ICU-acquired BSI compared to nondiabetic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
25
0
7

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 23 publications
3
25
0
7
Order By: Relevance
“…The search revealed nine publications that reported differences between men and women with respect to incidence of BSI (Table 5, available online). [23][24][25][26][27][28][29][30][31] Controlling for a variety of covariates, three of the articles reported that men had significantly higher infection rates than women, and six reported no significant gender differences. Although the majority found no significant gender differences, the fact that all studies reporting significant differences found that males were at higher risk suggests a possible association.…”
Section: Discussionmentioning
confidence: 99%
“…The search revealed nine publications that reported differences between men and women with respect to incidence of BSI (Table 5, available online). [23][24][25][26][27][28][29][30][31] Controlling for a variety of covariates, three of the articles reported that men had significantly higher infection rates than women, and six reported no significant gender differences. Although the majority found no significant gender differences, the fact that all studies reporting significant differences found that males were at higher risk suggests a possible association.…”
Section: Discussionmentioning
confidence: 99%
“…Besides being a major cause of urinary infection, Escherichia coli was also the main cause of generalized bacteremia and sepsis. Michalia and associates found that despite the strict control and regulation of blood glucose, diabetics 1,7 times more likely develop septicemia in the Intensive care unit, in comparison with patients without diabetes (5). …”
Section: Discussionmentioning
confidence: 99%
“…For example, chronic diabetic macro-and micro-vascular disease likely increases the heterogeneity of blood flow and tissue metabolism in acute sepsis. DM is suggested to be an independent risk factor for intensive care unit bloodstream infections (without increasing mortality) (19). However, DM may be associated with anti-inflammatory effects of exogenous insulin used for treating hyperglycemia, (20) offer renal protection against acute kidney injury, (21) decrease the incidence of acute lung injury, (22)(23)(24) and increase overall provider vigilance.…”
mentioning
confidence: 99%